Clinical trials: The conflict between the doctors’ financial interests of in recruiting patients and the patients’ best interests in Malaysia - Yusof, Yuhanif; Halim, Rohizan; Masum, Ahmad (2015)
The Hippocratic and the principle of beneficence require that doctors should always act in the patient’s best interest. However, once the ‘doctor’ puts on the hat of a ‘doctor-investigator’ by involving in clinical trials, the responsibility to safeguard the interests of the patient is no longer a priority.This is because the interest or intent of the doctor-investigator is different from that of the doctor who offers medical treatment solely in the best interests of patients.Instead, there are many interests of doctor-investigators, which include financial incentives in return for recruiting patients as research subjects.When there is a conflict between the financial interests of doctors in recruiting patients and patients’ best interests, ethical challenges to the integrity of doctor investigators may arise in making decision which is not bias. Hence, the objective of this paper is to discuss about conflict of interests between the doctor-investigator incentives to recruit and the doctor-investigator’s duty to keep the patients’ best interest.A qualitative methodology has been used in the process of writing this conceptual paper.The findings show that incentives gained by doctor-investigators in return for recruiting patients violate the principle of ethics because of the conflict of interests bearing in mind that the Hippocratic and the principle of beneficence require doctors to act in the patients’ best interest.